Effects of neem oil (Azadirachta indica A. Juss) on the replacement of the midgut epithelium in the lacewing Ceraeochrysa claveri during larval-pupal metamorphosis - Scudeler, Elton Luiz [UNESP]; Padovani, Carlos Roberto [UNESP]; Santos, Daniela Carvalho dos [UNESP] (Elsevier B.V., 2014)
Larvae of the lacewing Ceraeochrysa claveri were fed on eggs of Diatraeasaccharalis treated with neem oil at concentrations of 0.5%, 1% and 2% throughout the larval period. Pupae obtained from treated larvae were used in the study at five days after the completion of cocoon spinning to investigate the effects of neem oil on the replacement of the midgut epithelium during the larval-pupal transition. We observed that the old larval epithelium was shed into the midgut lumen and transformed into the yellow body. Old cells from the yellow body were destroyed by apoptosis and autophagy and were not affected by neem oil. However, neem oil did affect the new pupal epithelium. Cells from treated pupae showed cellular injuries such as a loss of microvilli, cytoplasmic vacuolization, an increase of glycogen stores, deformation of the rough endoplasmic reticulum and dilation of the perinuclear space. Additionally, the neem oil treatment resulted in the release of cytoplasmic protrusions, rupture of the plasma membrane and leakage of cellular debris into the midgut lumen, characteristics of cell death by necrosis. The results indicate that neem oil ingestion affects the replacement of midgut epithelium, causing cytotoxic effects that can alter the organism's physiology due to extensive cellular injuries. (C) 2014 Elsevier GmbH. All rights reserved.
Keywords: Apoptosis; Autophagy; Cellular injury; Digestive system; Lacewing; Necrosis